Analysis of Early Childhood Play Activities in Indonesia - Wahyuni, Desvi; Ardina, Mona; Novianti, Rahmah; Komala, Vivi Patra; Fitri, Arnita (PIAUD Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah, 2025)
This study aims to analyse various publications related to research discussing play activities in early childhood in Indonesia during the period 2015-2025. The research approach used in this study was qualitative, with a literature review based on data obtained from the Scopus database using Publish or Perish software. The results of the study show that publications related to play activities in early childhood in Indonesia occurred mostly in the period 2022-2025, with the highest number in 2025, namely 20 studies. After analysing the literature sources related to play in early childhood, the focus was on aspects of child development, which consisted of 11 studies. Thus, these findings illustrate that research related to play activities provided to children is still limited to the form of developmental stimulation. As a follow-up, the researchers hope that there will be more research that prioritises play activities as a child's right or children's wellbeing.